METHOD OF PERFORMING KEYED-HASH MESSAGE AUTHENTICATION CODE (HMAC) USING MULTI-PARTY COMPUTATION WITHOUT BOOLEAN GATES (2017)
The subject matter discloses a method operated on at least two servers for a third-party client, the method comprising receiving by a first server a first result of the first irreversible function applied to a secret key from a first third-party client, receiving by a second server a second result of the second irreversible function applied to the secret key from the third-party client, receiving by the first server, a message from a second third-party client, the first server computing a first hash function on said first result and on said message, and sending a result of the first hash function from the first server to the second server, the second server computing a second hash function on said second result and on the result of the first hash function sent from first server and outputting the result generated by second server as HMAC result.